Development of Digital Comics as a Media for Biology Learning of Environmental Change for Senior High School Students - Dewi, Linda Kusuma; Harini, Nugrahaningsih Wahyu (FMIPA UNNES, 2021)
This research is motivated by the revolution in education and distance learning. The education revolution 4.0 implements the use of technology-based learning. This is closely related to government policies to implement a distance learning system. It takes innovation and a variety of learning media that can be used for independent learning that is flexible, able to provide motivation and attraction for students to gain in-depth knowledge related to the theory that explained by teachers. Digital comic media was developed as a solution to this problem. The aims of this research are to analyze the validity and test the practicality of digital biology comic media on environmental change theory for Senior High School (SHS) students. This research was done at SMA Negeri 1 Kajen, with the design of research is the modified Research and Development method (R&D) of Sugiyono (2015). The small scale test was trial in 28 students with random sampling techniques. The data collection techniques used observation, interview and questionnaire techniques which were analyzed quantitatively and qualitatively. The results of the validity of the media expert got a very valid value of 94.1% and the theory expert got a valid value of 78.5%. The results of the practically test and the students' responses each obtained an average score of 86.74% and 94.2% in the very good category. The research results showed that the digital biology comic media was feasible and appropriate to be used as a biology learning media for environmental change theory.